Longitudinal Study on Quality of Life and Psychosocial Conditions in Light of Responses to Illness-Related Information in Postoperative Cancer Patients - Michiyo Mizuno; Jun Kataoka; Fumiko Oishi (Elsevier, 2018)
Objective: Illness-related information can be significant for cancer patients after gastrointestinal (GI) surgery in terms of their performing adaptive tasks. This study longitudinally investigated the health outcomes of Japanese patients who read a booklet about cancer patients' problems and adaption tasks and evaluated the association between the responses to the booklet and the patients' health outcomes. Methods: A questionnaire survey about quality of life (QOL), fatigue, anxiety, cognitive plight, and resilience was administered to postoperative patients with GI cancer 1 week after their discharge from hospital and 6 months after surgery. The questionnaires were returned by email. Results: The mean age of the 32 patients at 1 week was 60.9 years; nearly 68.8% of them were men. As a whole, only two variables, QOL and anxiety, were significantly improved at 6 months over those at 1 week. Three statements were taken to gauge the responses to the booklet. In the two-way ANOVA that took QOL and responses to the booklet as independent variables, the post hoc test found that QOL was significantly improved in patients who agreed with the statement "I vaguely understood the content" or "I will deal with my tasks as described in the scenarios" but not in patients who agreed with the statement "The scenarios reflect my situation." The anxiety in patients who agreed with the statement "The scenarios reflect my situation" was high at both survey points. Conclusions: This study suggests that associations between the responses to the informational booklet and patients' health outcomes partially indicate the directional property of how to support their information usage.